Analysis of Development of Various Types of Urban Electric Transport in Polotsk and Novopolotsk - D. V. Kapskiy; V. N. Kuzmenko; A. S. Krasilnikava; S. S. Semchenkov; E. N. Kot; O. N. Larin (Наука и техника)
The paper considers options for reducing environmental losses in Polotsk and Novopolotsk through the development of trolleybus and tram systems – various types of urban electric transport. In order to reduce the costs of creating transport (including charging) infrastructure, as well as operating costs, the effectiveness of such systems has been determined when using not only classic types of transport, but also hybrid buses, electric buses, duo-buses. Approaches and methods have been developed to improve the quality of passenger service without deteriorating the environmental situation – this will  become possible thanks to the development of tram and trolleybus traffic in Polotsk and Novopolotsk. Variants of scenarios for the use of various types of urban eclectic transport in the cities under study are presented, which will reduce investment  in vehicles and the cost of creating an operational base at the expense of existing production facilities, for example, a tram fleet. In addition, this will make it possible to create and organize a unique agglomeration rail passenger system, which can become one of the ways to develop the tourist potential of Polotsk and Novopolotsk. The proposals outlined in the paper  are aimed at improving the environmental situation in these cities by reducing the volume of emissions of harmful substances by buses, especially on the central streets.